Redescription and phylogenetic position of Ctenomys dorsalis Thomas 1900, an enigmatic tuco tuco (Rodentia, Ctenomyidae) from the Paraguayan Chaco (2019)
Ctenomys dorsalis is known only from its type specimen, a female preserved as skin without skull (except for the upper incisors) from an imprecise locality in the "Northern Chaco of Paraguay". Here, we report additional individuals of this species housed, since the 1940s, at the Field Museum of Natural History (Chicago, USA). Based on these specimens, which fully match the original description of this rodent, we provide novel information regarding its phylogenetic position, external and cranial morphology, and distribution. The analysis of mtDNA sequences supports the distinctiveness of this taxon and suggests its placement within the boliviensis group of Ctenomys. Our study highlights once more the importance of museum collections as repositories of biodiversity. © 2018 Walter de Gruyter GmbH, Berlin/Boston 2018.